Influence of glenosphere design and material on clinical outcomes of reverse total shoulder arthroplasty. Issue 3 (July 2014) - Bloch, Hans R; Budassi, Piero; Bischof, Andreas; Agneskirchner, Jens; Domenghini, Christian; Frattini, Marco; Borroni, Mario; Zoni, Sabine; Castagna, Alessandro
Background: The aim of this multicentre retrospective study was to compare reverse total shoulder arthroplasty clinical outcomes with glenospheres of different diameters, designs and materials. Methods: Between 2003 and 2008, 133 patients were divided into three groups: 60 (45%) with 36-mm standard CoCrMo (group A), 21 (16%) with 36-mm eccentric cobalt-chromium-molybdenum (CoCrMo) (group B) and 52 (39%) with 44-mm cross-linked ultra-high molecular weight polyethylene (X-UHMWPE) (group C) glenospheres. Mean (SD) follow-up was 38.7 (17.4) months. Clinical evaluation included Constant score and range of motion. Radiographic analysis included radiolucent lines, instability, loosening and assessment of scapular notching. Results: Mean Constant score significantly increased for all groups (Wilcoxon test, p  < 0.001). Group C allowed a higher and stable increase in range of motion. After 12 months and 24 months, groups C and B showed less pain than group A (Mann–Whitney U -test, p  < 0.05). Group C had significantly lower scapular notching than group B (Mann–Whitney U -test, p  = 0.001) and A (Mann–Whitney U -test, p  = 0.009) at 12 months, 24 months and 36 months. Groups A and C presented 5 (8.3%) and 4 (7.6%) early complications, respectively. Conclusions: The present study reported good results for all groups, although groups C and A presented better clinical outcomes, significantly lower notching and instability. A 44-mm X-UHMWPE glenosphere allowed a faster and more stable functional recovery, despite poorest pre-operative conditions. Additional long-term studies are needed to evaluate survivorship.